PERCEPTIONS OF SECONDARY SCHOOL STUDENTS FOR THE DEMOCRACY CONCEPT: A METAPHORIC STUDY - Recepoğlu, Serpil; Avci, Emine Karasu; B. Ünal Ibret (Zenodo, 2020)
Although democracy is generally defined as a form of government based on the sovereignty of the people, it is also a phenomenon that makes itself felt in all areas of life. It is possible for democracy to function in all segments of society with the existence of individuals who adopt democratic knowledge, skills, attitudes and values. A democratic culture of life can be achieved through schools and lessons. At this point, determining the perceptions of students who will be citizens of the future towards the concept of democracy will contribute to the formation of a democratic life culture. The aim of this study is to reveal the perceptions of secondary school students about the concept of democracy through metaphors. The study group of this research consists of 165 5th, 6th, 7th and 8th grade students who are continuing their education at a public school in Hilvan district of Şanlıurfa province in the spring term of 2016-2017 academic year. The participants were asked to fulfil the “Democracy is like …… because …..” expressions featured in the survey form. In this study, the obtained data were analyzed by descriptive analysis. In this study, secondary school students developed 53 metaphors for the concept of “democracy”. These metaphors are respectively the metaphors of freedom, equality, justice, life, election, republic, peace, politics, independence, scales, solidarity, country integrity and freedom of thought. When the metaphors were examined for the categories, students developed the most metaphor in the categories of democracy as a symbol of freedom and democracy as a tool of equality.
Keywords: 4. Education; 16. Peace & justice